Governance and participation in Yucatán, the case of participatory budgeting in Mérida - Zapata Godoy, Elías (Southern perspective / Perspectiva austral, 2024)
Introduction: Participatory budgeting represented an innovative mechanism for promoting citizen participation in public management. In Mérida, Yucatán, the program “Design your City” was implemented in the period 2023-2024, with the purpose of involving citizens in budgetary decision-making. Using a governance approach, the research analyzed the effectiveness of this model and its impact on the structure of local participation.Development: The study examined the formal and informal institutional arrangements that underpinned the participatory budget. Several key actors were identified, including the City Council of Mérida, autonomous bodies and civil society. The research was based on a qualitative analysis, using semi-structured interviews and documentary review to evaluate the participatory, collaborative, administrative, financial and legal dimensions of the program. It was found that the implementation of the model depended to a large extent on the capacity for coordination between institutions and citizens.Conclusions: The results indicated that participatory budgeting in Mérida promoted citizen participation, although with challenges in transparency and accountability. While consultation mechanisms were in place, the real influence of citizens on decision-making was limited. The governance of the process reflected a complex interaction between regulations and political-administrative practices, highlighting the need to strengthen the institutionalization of participatory budgeting to ensure its long-term impact.